2019
DOI: 10.1186/s13550-019-0490-0
|View full text |Cite
|
Sign up to set email alerts
|

18F-FLT PET/MRI for bone marrow failure syndrome-initial experience

Abstract: Background Bone marrow failure syndrome (BMFS) is a heterogeneous group of disorders associated with single- or multiple-lineage cytopenia and failure of normal hematopoiesis. We assessed the feasibility of integrated PET/MRI with 3′-deoxy-3′- 18 F-fluorothymidine ( 18 F-FLT) to assess the pathophysiology of whole-body bone marrow for the diagnosis and monitoring of BMFS. Twenty-five consecutive patients with BMFS underwent a pre-treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 19 publications
2
17
0
Order By: Relevance
“…An increased uptake in vertebral body uptake 3 to 4 weeks after chemotherapy was indicative of increased proliferative activity consequent to marrow recovery after chemotherapy, as was also observed in other studies [35,36]. An increase in the splenic FLT uptake paralleled that in the vertebral body; this is more likely to reflect the FLT activity in the blood pool, although a potential role in haematopoiesis cannot be completely ruled out without corroborative tissue data.…”
Section: Discussionsupporting
confidence: 82%
“…An increased uptake in vertebral body uptake 3 to 4 weeks after chemotherapy was indicative of increased proliferative activity consequent to marrow recovery after chemotherapy, as was also observed in other studies [35,36]. An increase in the splenic FLT uptake paralleled that in the vertebral body; this is more likely to reflect the FLT activity in the blood pool, although a potential role in haematopoiesis cannot be completely ruled out without corroborative tissue data.…”
Section: Discussionsupporting
confidence: 82%
“…Regarding the etiology of splenomegaly, a study using 99m Tc-red blood cell (RBC) and 113m In-heat-damaged RBC scintigraphy demonstrated a significant correlation between splenic size and hypervascularization in both MF and PV, whilst a correlation with hypercellularity was only seen in MF [ 71 ]. In line with these findings, variably increased splenic uptake of 18 F-FDG, 18 F-FLT and 111 In-Cl3 has been demonstrated in MF, often combined with low axial and/or high peripheral BM uptake [ 27 , 28 , 30 , 35 39 ]. Lastly, increased splenic membrane metabolism was suspected in one PV and three MF patients because of increased phosphomonoester/Pi and phosphomonoester/B-ATP ratios as measured by splenic 31-phosphor MRS [ 72 ].…”
Section: Resultssupporting
confidence: 60%
“…Dixon quantitatively confirmed markedly decreased fat fractions in a few patients [ 33 , 34 ]. Diffusion-weighted MRI showed increased BM signals in two patients [ 35 ]. On short-tau inversion recovery (STIR) images, skeletal signals ranged from high tot low [ 8 , 31 , 32 ], and were presumed to reflect the degree of cellularity [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 18 F]FDG PET reveals glycolytic activity, DWI reflects the restricted random movement of extra-cellular water protons (cellular density), PDFF measurements assess the fat content, and R2* reflects the level of iron deposition. The recent introduction of integrated PET/MRI has enabled simultaneous whole-body bone-marrow PET and functional MR imaging in bone-marrow disorders 5 , 6 . Therefore, physiological factors influencing bone-marrow [ 18 F]FDG uptake and MR signals and the associations should be clarified for accurate diagnosis.…”
Section: Introductionmentioning
confidence: 99%